Impact of EGFR and EGFR ligand expression on treatment response in patients with metastatic colorectal cancer - Klupp, Fee; Saß, Malte Christian; Bergmann, Frank; Khajeh, Elias; Ghamarnejad, Omid; Hassenpflug, Matthias; Mehrabi, Arianeb; Kulu, Yakup (Oncology letters, 2021)
Up to 50% of patients with colorectal cancer (CRC) have either synchronous or metachronous hepatic metastases in the course of their disease. Patients with metastatic CRC (mCRC) whose tumors express wild‑type KRAS benefit from treatment with monoclonal antibodies (such as cetuximab or panitumumab) that target the epidermal growth factor receptor (EGFR). However, the therapeutic response to these antibodies is variable, and further predictive models are required. The present study examined whether expression of different EGFRs or their ligands in tumors was associated with the response to cetuximab treatment. Tumor tissues, collected during liver resection in 28 patients with mCRC, were analyzed. The protein expression levels of EGFR/ErbB1, ErbB2, ErbB3 and the EGFR ligands heregulin and amphiregulin were determined using Luminex 200® and enzyme‑linked immunosorbent assays. Computed tomography or magnetic resonance imaging was performed 4 weeks before and 6‑8 weeks after treatment with cetuximab. Response to treatment was assessed using the response evaluation criteria for solid tumors (RECIST). The association between the protein expression levels of different EGFRs and their ligands with RECIST criteria was then analyzed to determine whether these protein levels could predict the treatment response to cetuximab. A total of 12 patients exhibited a partial response, 9 exhibited stable disease and 7 exhibited progressive disease after cetuximab therapy according to RECIST. The expression levels of EGFRs (EGFR/ErbB1, ErbB2 and ErbB3) and their ligands (heregulin and amphiregulin) were not significantly associated with the response to cetuximab therapy. Therefore, the present study indicated that EGFR or EGFR ligand expression did not predict treatment response in patients with CRC with liver metastases following cetuximab therapy.